Peran Guru PAI Mendisiplinkan Siswa dalam Pelaksanaan Shalat Berjamaah di SMP Negeri 5 Sungai Limau - Nursyda, Filda; Rivauzi, Ahmad (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the role of Islamic Education (PAI) teachers in fostering students’ discipline in religious practices within the school environment, despite its significant impact on the development of students' religious character. The purpose of this study is to describe the role of PAI teachers in teaching, cultivating awareness of, and supervising the implementation of congregational Zuhur prayer among students at SMP Negeri 5 Sungai Limau. A qualitative method with a phenomenological approach was employed, involving 165 students and teachers as participants. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The findings reveal that PAI teachers play a role in three main aspects: first, teaching prayer discipline through direct instruction and role modeling; second, fostering religious awareness through motivation and spiritual habituation; and third, monitoring discipline by recording attendance and applying sanctions for non-compliance. These findings support Thomas Lickona’s character education theory, which comprises moral knowing, moral feeling, and moral action. The study concludes that the success of cultivating students’ discipline in worship is highly influenced by the consistency, exemplary conduct, and humanistic approach of PAI teachers. The implications include a theoretical contribution to the literature on character education based on religiosity, as well as practical recommendations for schools and parents to strengthen synergy in creating a supportive worship environment. This study also opens avenues for further research on the influence of social environment and family roles in shaping students’ religious discipline.